Industry influence on materiality level determination in the process of financial statements audit - Kaziukonis, Gytis; Jurkonienė, Gerda (Buhalterinės apskaitos teorija ir praktika, 2020)
Materiality levels are being used by auditors in different financial statement audit planning, procedure performance and results measurement stages. Thus, ensuring that financial statements are not significantly distorted. International standards on auditing contain extensive levels in materiality interpretation however, when determining materiality, it is underlined that auditor must be versed about audited company‘s sector and industry. The aim of the research is to analyze the industry factors which influence materiality determination levels in financial statement audit process and to establish the scheme of industry influence on materiality level determination. An article applies information collection, systematization and interpretation methods, analysis of Lithuanian and foreign scientific literature, audit regulatory legal acts. The analysis enabled to determine that industry significantly influence both planning and performance materiality also the allocation of the latter for accounting articles. The influence is determined by qualitative and quantitative industry factors. Theoretical model of industry influence on materiality determination is submitted in the framework below.
Keywords: financial statements; materiality; industry; planning materiality; performance materiality